TASAWUF AL-GHAZALI : LANDASAN PSIKOLOGI PENDIDIKAN ISLAM - Ghofur, Abdul (JURNAL ISLAM NUSANTARA, 2018)
Al-Ghazali as a philosopher, thinker and his life ended ascetic is one of a row of name having service exceptional in science, chiefly Moslem. In his hands, science was developing, interesting and live. Psychology as a branch of science has correlation in the knowledge referred to Al-Ghazali through his book which until now were interested in it by the search continues in the intellectual are able to present, his presence colored the Islamic world thought mainly through the work of his Magnum Opus â€œIhya Ulumuddinâ€. People grow and flourish, exist, build their lives and work is cannot be separated from human behavior itself. Stupid and disadvantaged is also caused by human behavior itself, so as to be very important that man must be to develop themselves and not order to complete. Education has the big role to increase the human life thatâ€™s way the psychology get big role to perfect the results.